A large, high-gain, 400 mm single-aperture slab amplifier with 20 kJ laser output. (August 2022) - Chen, Lin; Qiang, Yongfa; Wu, Wenlong; Zhao, Junpu; Liu, Jianguo; Wang, Zhenguo; Li, Sen; Liu, Yong; Lin, Wang; Liu, Qiang
Highlights: A high gain output is achieved by obtaining optimal combination of slab amplifier parameters using an optimization model. The average small signal gain coefficient is 5.65%/cm, which is higher than other 400 mm single-aperture slab amplifiers. A uniformly distributed near-field output is achieved after compensating the gain nonuniformity by reshaping the near-field. The output energy reaches 20.4kJ/4.5TW/1053 nm, with a near-field modulation degree of 1.40:1 and a contrast degree of 0.085. Abstract: This paper introduces a slab laser amplifier system of 400 mm single-aperture in the Integration Test Bed (ITB) laser facility. Based on the theoretical optimization model for parameters, the system uses flash-lamps with the diameter is 31 mm and the pump pulse width is 480 μs, the average small signal gain coefficient in the aperture of laser beam is 5.65%/cm. A uniformly distributed near-field output of laser can be achieved by adjusting the near-field of seed laser. The energy output reaches 20.4 kJ/4.5TW/1053 nm, the near-field modulation is 1.40:1, and the near-field contrast is 0.085.